Phenolic Compounds from Sonchus arvensis Linn. and Hemerocallis citrina Baroni. Inhibit Sucrose and Stearic Acid Induced Damage in Caenorhabditis elegans - Qin An; Lei Zhang; Xiyue Qin; Xiong Wang; Wenli Wang; Qingyong Meng; Yali Zhang (Molecules, 2023)
Sonchus arvensis Linn. and Hemerocallis citrina Baroni. have been reported to improve body resistance. However, the underlying mechanism is not clear. In this study, Sonchus arvensis Linn. phenolic compounds (SAP) and Hemerocallis citrina Baroni. phenolic compounds (HCP) were extracted and their protective effects in Caenorhabditis elegans evaluated. SAP and HCP showed considerably different phenolic compositions. In the normal C. elegans model, HCP exhibited better effects in promoting growth than SAP. In the sucrose-incubated C. elegans model, both SAP and HCP showed positive effects against the high-sucrose-induced damage. In the stearic acid-incubated C. elegans model, both SAP and HCP improved lifespan, reproductive ability and growth, while HCP had a more evident effect than SAP on reproductive ability. The TGF-β signaling pathway was confirmed to be involved in the protective effects of SAP and HCP. The antioxidant ability of SAP was also found to be related to skn-1. Our study shows that both SAP and HCP have protective effects against high sucrose- or high stearic acid-induced damage.